Cantú syndrome: Findings from 74 patients in the International Cantú Syndrome Registry. Issue 4 (11th December 2019) - Grange, Dorothy K.; Roessler, Helen I.; McClenaghan, Conor; Duran, Karen; Shields, Kathleen; Remedi, Maria S.; Knoers, Nine V. A. M.; Lee, Jin‐Moo; Kirk, Edwin P.; Scurr, Ingrid; Smithson, Sarah F.; Singh, Gautam K.; et al.
Abstract: Cantú syndrome (CS), first described in 1982, is caused by pathogenic variants in ABCC9 and KCNJ8, which encode the regulatory and pore forming subunits of ATP‐sensitive potassium (KATP ) channels, respectively. Multiple case reports of affected individuals have described the various clinical features of CS, but systematic studies are lacking. To define the effects of genetic variants on CS phenotypes and clinical outcomes, we have developed a standardized REDCap‐based registry for CS. We report phenotypic features and associated genotypes on 74 CS subjects, with confirmed ABCC9 variants in 72 of the individuals. Hypertrichosis and a characteristic facial appearance are present in all individuals. Polyhydramnios during fetal life, hyperflexibility, edema, patent ductus arteriosus (PDA), cardiomegaly, dilated aortic root, vascular tortuosity of cerebral arteries, and migraine headaches are common features, although even with this large group of subjects, there is incomplete penetrance of CS‐associated features, without clear correlation to genotype.